TECNOLOGIAS DIGITAIS NAS PRÁTICAS PEDAGÓGICAS EM TEMPOS DE PANDEMIA DA COVID-19: Um estudo com professores do curso de técnico em Administração de uma unidade escolar pública do Estado do Maranhão - LEITE, Alysson Santos (2024)
The research deals with the use of Digital Information and Communication Technologies (DIT) in pedagogical practices in times of the COVID-19 pandemic in the Administration technician course whose field of study is the Institute of Education, Science and Technology of Maranhão (IEMA) Bacabeira/MA unit. The general objective of the research was to verify the relationships between high school teachers of the Administration technician course at the Institute of Education, Science and Technology of Maranhão (IEMA), located in the municipality of Bacabeira/MA, with the integration of TDIC into their pedagogical practices. during the COVID-19 pandemic period. As for the methodological procedures outlined, this research is configured as applied, bibliographic and case study. The subjects of the research were the 5 teachers who make up the staff of the Administration technician course at the IEMA unit of Bacabeira/MA. The data collection instruments for obtaining information from the subjects were: interviews, questionnaires and document analysis. Data analysis and interpretation were carried out using texts, response tables and tables. Where we obtained responses from teachers of the Administration technician course at IEMA in the Bacabeira/MA unit: A positive overview of the use of TDIC (Google Meet, WhatsApp, YouTube and Instagram) in their pedagogical practices; Attention to environmental changes and availability to search for viable solutions arising from the problems caused by the COVID-19 pandemic; New perspectives on the use of TDIC after the pandemic period in Administration classes; Provision of topics related to TDIC for the development of future studies. Furthermore, we developed the educational product, which consists of a digital didactic-pedagogical booklet containing guidance on the TDIC most used by teachers of the Administration technician course at the IEMA unit of Bacabeira/MA during the COVID-19 pandemic period, aiming to constantly contribute to their pedagogical practices.